Childcare Facilities for Young Children in France: History, Current State, and Prospects - Daria Druzhinenko-Silhan; Patrick Schmoll (Национальный психологический журнал)
Background. This article delves into the evolution of extra-familial childcare in France since the 19th century, reflecting on the socio-economic pressures and societal values that have shaped its development. It highlights how France's approach to childcare is deeply interwoven with its social policies, economic developments, and changing family structures. Objective. The main aim is to analyze the historical trajectory and current state of childcare systems in France, addressing the dynamic interplay among policy, societal needs, and economic factors. It also assesses how these elements influence the quality and availability of childcare. Methods. The study reviews existing data on childcare utilization, policy impacts, and demographic trends affecting children under three years of age in France. The methodology includes a comprehensive review of historical documents, policy analyses, and current statistical data from organizations like ONAPE (l’Observatoire national de la petite enfance) and DREES (Direction de la recherche, des études, de l'évaluation et des statistiques) to construct a detailed picture of the childcare landscape in France. Results. The research reveals that France has one of the highest childcare coverage rates in the OECD, facilitated by a mix of public and private provisions. However, recent shifts towards privatization have sparked debates concerning the quality of care and commercialization risks. Current systems face challenges due to economic constraints and changing demographic patterns, with a notable trend towards increased private sector involvement in childcare services. Conclusions. While France has made significant strides in providing childcare, ongoing economic pressures and evolving social norms continue to shape its landscape. The balance between public welfare and private enterprise, alongside the quality of childcare, remains a critical area for future policy and societal debate. As France continues to adapt to these challenges, the trajectory of its childcare systems will likely serve as a bellwether for broader social policy shifts in the country.